Evolyutsiya nauchnykh predstavlenii ob ob''ekte i krizis obshchei teorii fizicheskoi kul'tury - Natalov, G. G. (Teorija i Praktika fiziceskoj Kul'tury, 1998)
The reasons of the contemporary physical culture theory`s crisis and the ways to overcome it are considered in this article.